Future approaches to evaluating tourism in the developing world: Assessing realism in the Solomon Islands. (March 2022) - Warne, Sarah Jane; Thompson, Michelle
Abstract: Tourism is often used as a tool for economic growth and development. However, evaluating the effectiveness of tourism interventions to deliver intended benefits, and contribute to outcomes such as poverty alleviation, continue to be debated. This research examined the advantages of using the realist evaluation methodology when assessing tourism as an intervention in a developing country. An inductive research approach based on the Context, Mechanism and Outcome (C-M-O) configuration was used to capture stakeholders' views about the benefits and beneficiaries of tourism interventions in the Solomon Islands. This research demonstrates how the realist evaluation methodology may be used to develop a holistic understanding of the effectiveness of tourism interventions by evaluating what works, for whom, how and in what circumstances and respects. This understanding has practical implications for development partners to inform decision-making that enhances the effectiveness of tourism interventions to deliver greater benefits to local communities.